2004
DOI: 10.1007/s00299-004-0867-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiple spindles and cellularization during microsporogenesis in an artificially induced tetraploid accession of Brachiaria ruziziensis (Gramineae)

Abstract: The genus Brachiaria is characterized by a majority of polyploid accessions--mainly tetraploid--and apomictic reproduction. Sexuality is found among diploids. To overcome incompatibility barriers, accessions with the same ploidy level are necessarily used in hybridization. Thus, sexual diploid accessions were tetraploidized to be used as female genitors. This paper reports microsporogenesis in an artificially induced tetraploid accession of Brachiaria ruziziensis. Chromosome pairing at diakinesis ranged from u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 18 publications
1
29
2
Order By: Relevance
“…In such cases, the chromosome behavior at meiosis is expected to be random or not in any preferential form (polyssomic inheritance) (Albinic et al 2006), with a tendency to form multivalents (Ramsey and Schemske 2002). However, the predominance of bivalent associations suggests a genetic control of chromosome pairing such as has been recognized in artificially induced autotetraploids of Trifolium riograndense Moraes-Fernandes 1986, 1987), of B. brizantha (Araújo et al 2005), and of B. ruziziensis (Risso-Pascotto et al 2005). In 20 accessions of natural tetraploid B. nigropedata (2ni=i 4xi=i36), bivalent associations also predominated in diakinesis, suggesting that its origin was possibly as a segmental allopolyploid (Utsunomiya et al 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, the chromosome behavior at meiosis is expected to be random or not in any preferential form (polyssomic inheritance) (Albinic et al 2006), with a tendency to form multivalents (Ramsey and Schemske 2002). However, the predominance of bivalent associations suggests a genetic control of chromosome pairing such as has been recognized in artificially induced autotetraploids of Trifolium riograndense Moraes-Fernandes 1986, 1987), of B. brizantha (Araújo et al 2005), and of B. ruziziensis (Risso-Pascotto et al 2005). In 20 accessions of natural tetraploid B. nigropedata (2ni=i 4xi=i36), bivalent associations also predominated in diakinesis, suggesting that its origin was possibly as a segmental allopolyploid (Utsunomiya et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…ruziziensis, irregular chromosome segregation in the two meiotic divisions led to the development of polyads as the final meiotic product and pollen sterility reached 63.38% (Risso- Pascotto et al 2005). In the natural tetraploid B. decumbens cv Basilisk, many cells with precocious chromosome migration to the poles at metaphase I and Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…RISSO-PASCOTTO et al (2003) suggest that non-oriented chromosomes result from a linking failure of spindle fibers to the kinetochore, making them disperse in the cytoplasm.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of irregular chromosome behavior in metaphases and anaphases in the Euphorbiaceae family was observed by NASSAR (2000) in a cytogenetic and evolutive study of Manihot esculenta Crantz, where there was precocious chromosome migration in metaphase I and II, and laggard chromosomes in anaphase I and II. RISSO-PASCOTTO et al (2005), in an analysis of Ciência Rural, v.42, n.6, jun, 2012. microsporogenesis in Brachiaria ruziziensis, it was reported the occurrence of precocious chromosome migration and laggard chromosomes.…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of meiosis in tetraploidized accessions of B. ruziziensis (Risso-Pascotto et al, 2005a;Pagliarini et al, 2008) has revealed numerous abnormalities that are mainly related to irregular segregation. Furthermore, meiotic behavior is genotype-specific.…”
Section: Introductionmentioning
confidence: 99%